MHC-B variation in maternal and paternal synthetic lines of the Argentinian Campero INTA chicken - Iglesias, Gabriela Marisa (2021)
Fil: Iglesias, Gabriela Marisa. Universidad Nacional de Río Negro. Río Negro, Argentina